National Library of Singapore (Singapore : National Library Board, 1999)
This program shows the National Library of Singapore rules that practice to their users. Also included some good library habits that can be shared
System requirements: Microsoft Windows 95 platform with'Active Movie' software, 16-Bit sound card, CD-ROM drive, Fast VGA card with at least 1 MB RAM
VCD format
Keywords: Libraries -- Singapore; Singapore -- Libraries